2022
DOI: 10.1007/s11606-021-07329-9
|View full text |Cite
|
Sign up to set email alerts
|

The Abrupt Expansion of Ambulatory Telemedicine: Implications for Patient Safety

Abstract: The exponential growth of telemedicine in ambulatory care triggered by the COVID-19 public health emergency has undoubtedly impacted the quality of care and patient safety. In particular, the increased adoption of remote care has impacted communication, care teams, and patient engagement, which are key factors that impact patient safety in ambulatory care. In this perspective, we draw on a scoping review of the literature, our own clinical experiences, and conversations with patient safety experts to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Telemedicine has expanded in recent years as access and need have increased, and evidence for comfort and efficacy have improved. [1][2][3][4][5][6][7][8][9][10] Although data privacy in telemedicine has been an anticipated concern, communication privacy in telemedicine is not well-studied. However, patients are now attending their appointments from grocery stores, dog parks, and coffee houses (Potkin in submission).…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has expanded in recent years as access and need have increased, and evidence for comfort and efficacy have improved. [1][2][3][4][5][6][7][8][9][10] Although data privacy in telemedicine has been an anticipated concern, communication privacy in telemedicine is not well-studied. However, patients are now attending their appointments from grocery stores, dog parks, and coffee houses (Potkin in submission).…”
Section: Introductionmentioning
confidence: 99%
“…PHCPs also highlighted concerns that remote assessments could not provide the same level of detail as face-to-face assessments, which may lead to misdiagnosis. Though more data specifically on patient safety related to the use of telemedicine in perinatal care is needed, concerns over patient safety in relation to telemedicine have already been raised in other areas of healthcare during COVID-19 [32]. In the present study, PHCPs also identified internet and mobile data charges as a significant barrier to many young parents' ability to engage with telemedicine.…”
Section: Discussionmentioning
confidence: 68%
“…The misdiagnosis is issued by only 26.3% of the selected studies. Given the increase in teleconsultation, the lack of interest in this field deserves a specific mention [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%